2018
DOI: 10.1177/2325967118808242
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Superior Capsular Reconstruction With a Minimally Invasive Harvested Fascia Lata Autograft Produces Good Clinical Results

Abstract: Background:Painful dysfunctional shoulders with irreparable rotator cuff tears (IRCTs) in active patients are a challenge. Arthroscopic superior capsular reconstruction (ASCR) is a new treatment option originally described using a fascia lata autograft harvested through an open approach. However, concerns about donor site morbidity have discouraged surgeons from using this type of graft.Hypothesis:ASCR using a minimally invasive harvested fascia lata autograft produces good 6-month and 2-year shoulder outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
189
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(194 citation statements)
references
References 49 publications
4
189
0
1
Order By: Relevance
“…Similar to our study, four recent publications about SCR with human dermal allografts reported failure rates between 40 and 60% with mainly humeral side ruptures [4,11,15,25], while recent data on SCR with fascia lata autografts described failure rates between 5 and 10% [3,18]. Although the literature on SCR with fascia lata is limited, the healing rate of autografts seems to be far better.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our study, four recent publications about SCR with human dermal allografts reported failure rates between 40 and 60% with mainly humeral side ruptures [4,11,15,25], while recent data on SCR with fascia lata autografts described failure rates between 5 and 10% [3,18]. Although the literature on SCR with fascia lata is limited, the healing rate of autografts seems to be far better.…”
Section: Discussionsupporting
confidence: 88%
“…However, when using autografts, donor site morbidity, especially when taking a long fascia lata graft, needs to be considered. In fact, Azevedo et al [3] reported that at the 2-year follow-up, 57% of patients were still bothered by their harvested thigh and 76% noticed donor site changes. However, Plachel et al [26,27] in their case report showed that there is ingrowth of vessels and expression of growth factors in the acellular human dermal allograft patch after 6 months, which led them to the conclusion that healing of the graft to the native tissue may be facilitated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…His ingenious solution was the SCR, which was a minimally invasive, joint-preserving option that the rest of the world would soon adopt as a legitimate alternative to the RSA and tendon transfers. [3][4][5][6][7][8] To further complicate the issue, stringent regulation and lack of tissue banks limit the availability of allograft tissue in Japan. To meet this challenge, Mihata used fascia lata autograft to reconstruct the superior capsule.…”
Section: See Related Article On Page 579mentioning
confidence: 99%
“… 29 These individual variations in the thickness of FLA and technical challenges related to preparation of the graft makes standard FLA not always reproducible and a reliable option. 25 , 29 , 30 , 31 In our quest to find an improved biological autograft with higher structural strength, stiffness, and thickness, we designed a new graft based on the FL and reinforced with a nonresorbable suture mesh. We aimed to make a stiffer graft with right thickness, but without harvesting a large portion of the FL or disrupting the superior attachment of the tensor fascia lata muscle.…”
mentioning
confidence: 99%